Determinants of actual usage of BIM in the construction industry in Sabah - Nur-ul Balqes Md Zaid; Noraini Hamzah; Muhamad Azry Khoiry; Nelson Lajuni (Communications on Applied Nonlinear Analysis, 2025)
The purpose of this study was to investigate the impact of perceived utility (PU) and perceived ease of use (PEOU) on actual utilization (AU) of Building Information Modeling (BIM) in the Sabah construction industry. Additionally, the study explored the potential mediating effect of PEOU and AU on AU. This study used quantitative methodology to survey 30 BIM practitioners working in Sabah’s construction sector. The hypothesized hypotheses were tested using partial least squares structural equation modeling (PLS-SEM) using reflective indicators. Actual usage (AU) of BIM was positively influenced by perceived utility (PU) (LLCI = 0.725, ULCI = 0.849), whereas PEOU had no significant effect on AU (LLCI = -0.642, ULCI = 0.048). Additionally, the analysis revealed that in Sabah's construction sector, the notion of PU served as an intermediary between the concept of PEOU and the implementation of BIM (LLCI = 0.400, ULCI = 0.988). The results of this study offer significant contributions to the knowledge base of stakeholders and decision-makers regarding the determinants that impact the implementation of BIM in Sabah. Moreover, they can serve as a guide for developing effective strategies to promote BIM usage in the construction industry.